Current studies in Chinese language and discourse global context and diverse perspectives - Xiao, Yun (Linguist); Tsung, Linda T. H., 1953- (Studies in Chinese language and discourse ;, 2019)
"This volume features a discourse empirical orientation from diverse perspectives and various methodologies, in which narratives, interviews, surveys, and large-scale databases or self-created written and spoken corpora are employed and analyzed to gain a better understanding of new developments and changes in the Chinese language and discourse. Authors employ updated approaches from a variety of fields, including applied linguistics, functional linguistics, corpus linguistics and sociolinguistics, to describe the structure of the Chinese language and discourse and to examine its critical issues, many focusing on globalization-induced language developments and changes. With an empirically-based discourse/socio-cultural approach, this collection makes valuable contributions to research on Chinese language and discourse and serves as a sound reference for Chinese researchers and educators in diverse fields such as Chinese language and discourse, Chinese linguistics and language education, Chinese multiculturalism, and more"--